IMPLEMENTASI GERAKAN LITERASI SEKOLAH SEBAGAI PENANAMAN MINAT BACA SISWA KELAS IV - Berliana, Arvi Okta (Joyful Learning Journal, 2019)
Penelitian ini bertujuan untuk mengkaji implementasi GLS dalam menanamkan minat baca siswa kelas IV SD Negeri Tegalsari 02. Jenis penelitian ini adalah kualitatif deskriptif. Subjek dalam penelitian ini yaitu kepala sekolah, guru, dan siswa. Teknik pengumpulan data menggunakan observasi, wawancara, angket, dan dokumentasi. Pengujian keabsahan data menggunakan uji kredibilitas dan uji komfirmabilitas. Teknik analisis data menggunakan model Miles and Huberman. Hasil penelitian menunjukan bahwa, (1) GLS dalam menanamkan minat baca siswa dapat diamati dari kondisi siswa yang antusias, keinginan siswa membaca mulai muncul, adanya pemanfaatan sumber bacaan, dan adanya pengaruh lingkungan sosial, (2) kekuatan GLS dalam menanamkan minat baca yaitu pembiasaan, motivasi guru, penyediaan pojok baca sedangkan kelemahan GLS dalam menanamkan minat baca yaitu kurangnya jumlah buku, kurangnya motivasi orang tua, metode menanggapi bacaan kurang bervariasi. Penelitian ini menyimpulkan Gerakan Literasi Sekolah di SD Negeri Tegalsari 02 dinilai dapat menanamkan minat baca meski belum optimal karena masih terdapat kelemahan. The research was purposed to reviewing the implantation of SLM in implating the reading interest on fourth grade students of Tegalsari 02 Elementary School.This type of research is descriptive qualitative.The subjects in this study were the headmaster, the teacher, and the students.The technique of collecting data used observation, interviews, field notes, questionnaires, and documentation.Testing the validity of the data uses credibility tests and confirmation tests.The data analysis technique uses the interactive model by Miles and Huberman.The results showed that, (1) SLM on implanting students' reading interest could be observed from the condition of students who are enthusiastic, the desire of student’s reading begins to emerge, utilization of reading resources and the influence of social environment, (2) the power of SLM on implanting reading interest, namely habituation, teacher motivation, provision of reading corners. While the weaknesses are the lack of books, lack of motivation of parents, the method of responding to reading is less varied. The research concluded that SLM in Tegalsari 02 Elementary School was considered able to instill reading interest and discipline although wasn’t optimal because there were still weaknesses. The research was purposed to reviewing the implantation of SLM in implating the reading interest on fourth grade students of Tegalsari 02 Elementary School.This type of research is descriptive qualitative.The subjects in this study were the headmaster, the teacher, and the students.The technique of collecting data used observation, interviews, field notes, questionnaires, and documentation.Testing the validity of the data uses credibility tests and confirmation tests.The data analysis technique uses the interactive model by Miles and Huberman.The results showed that, (1) SLM on implanting students' reading interest could be observed from the condition of students who are enthusiastic, the desire of student’s reading begins to emerge, utilization of reading resources and the influence of social environment, (2) the power of SLM on implanting reading interest, namely habituation, teacher motivation, provision of reading corners. While the weaknesses are the lack of books, lack of motivation of parents, the method of responding to reading is less varied. The research concluded that SLM in Tegalsari 02 Elementary School was considered able to instill reading interest and discipline although wasn’t optimal because there were still weaknesses.